Pengaruh Sumber Daya Manusia Ramah Lingkungan (GHRM) Terhadap Kinerja Karyawan Melalui Keterlibatan Kerja Sebagai Variabel Intervening - Arviansyah, Bima; Saraswati , Shintya Dewi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Background: Green Human Resources Management is a workforce that understands, appreciates and practices environmentally friendly initiatives and maintains goals throughout the human resources process including recruiting, training, managing talented employees, compensation and separation. Employee performance is the result of the work achieved by employees in carrying out the obligations given by the company to its workers which are based on skill, experience, perseverance and time. Employee performance is the result of the behavior of company employees, where changing behavior for the better is the main priority. Work involvement focuses more on a high level of enthusiasm which is reflected in work activities (vigor and absorption), as well as a high level of joy in doing work. Objective: to analyze and prove whether work engagement can be an intervening variable between green human resource management and employee performance for UMKM. Method: The sampling technique uses a total sampling of 100 respondents. This research uses a quantitative approach with data analysis methods in the form of descriptive statistical analysis and regression analysis. Results: prove that green human resources have a positive influence on employee performance, green human resources have a positive influence on work engagement, work engagement has a positive influence on employee performance, work engagement is able to mediate the influence of green human resource management on employee performance.